Upaya Kepala Sekolah dalam Meningkatkan Disiplin Guru di SMPN 2 Sungai Tarab - Febrian, Vicky Rizki; Khairat, Annisaul; Arisandi, Dino (Jurnal Manajemen Pendidikan Islam (MANAPI), 2025)
In the implementation of education there are several components that can effectively and efficiently support the success of the teaching and learning process. This success is largely focused on educational leaders (school principals) who can carry out their roles and responsibilities. Therefore, as a manager, you must play a leadership role effectively to influence subordinates in achieving common goals. The purpose of this research is to determine the planning, implementation and evaluation of school principals in improving teacher discipline This research involves questions that need to be answered by certain sources or information providers, so this qualitative method is very necessary in this research. Because the qualitative method uses interviews to collect data, this is the main technique in the qualitative method. Through this research, it can be concluded that 1) Planning, the principal in disciplining teachers consists of the principal formulating rules and codes of ethics that are guided by the Law on the Minister of Education and Culture, 2) Implementation, the principal disciplining teachers using 3 approaches the example of the principal, routine training and motivation of the principal, and 3) Evaluation, in the evaluation activity of disciplining teachers, the principal carries out forms of evaluation activities such as monitoring, data collection and confirmation, and also collaborates with a team of supervisors/supervisors to assess performance teacher, which also includes teacher discipline.